Light‐driven tipping points in polar ecosystems. (20th October 2013) - Clark, Graeme F.; Stark, Jonathan S.; Johnston, Emma L.; Runcie, John W.; Goldsworthy, Paul M.; Raymond, Ben; Riddle, Martin J.
Abstract: Some ecosystems can undergo abrupt transformation in response to relatively small environmental change. Identifying imminent 'tipping points' is crucial for biodiversity conservation, particularly in the face of climate change. Here, we describe a tipping point mechanism likely to induce widespread regime shifts in polar ecosystems. Seasonal snow and ice‐cover periodically block sunlight reaching polar ecosystems, but the effect of this on annual light depends critically on the timing of cover within the annual solar cycle. At high latitudes, sunlight is strongly seasonal, and ice‐free days around the summer solstice receive orders of magnitude more light than those in winter. Early melt that brings the date of ice‐loss closer to midsummer will cause an exponential increase in the amount of sunlight reaching some ecosystems per year. This is likely to drive ecological tipping points in which primary producers (plants and algae) flourish and out‐compete dark‐adapted communities. We demonstrate this principle on Antarctic shallow seabed ecosystems, which our data suggest are sensitive to small changes in the timing of sea‐ice loss. Algae respond to light thresholds that are easily exceeded by a slight reduction in sea‐ice duration. Earlier sea‐ice loss is likely to cause extensive regime shifts in which endemic shallow‐water invertebrate communities are replaced by algae, reducing coastal biodiversity and fundamentally changing ecosystem functioning. Modeling shows that recent changes in ice and snow cover have already transformed annual light budgets in large areas of the Arctic and Antarctic, and both aquatic and terrestrial ecosystems are likely to experience further significant change in light. The interaction between ice‐loss and solar irradiance renders polar ecosystems acutely vulnerable to abrupt ecosystem change, as light‐driven tipping points are readily breached by relatively slight shifts in the timing of snow and ice‐loss.